Peran Linear Programming Metode Simpleks Dalam Mengoptimalisasi Keuntungan Pada Inovasi Bisnis Model - Siti Anggi Wulandari; Defriyanto Defriyanto; Suherman Suherman (Inovasi Pembangunan : Jurnal Kelitbangan, 2019)
The research aims to find out the maximum profits in startup model business by using linear programming in simplex method. The type of research are field and literature based study by observation, examining journals, and text books in relation to the researched-project. The steps undergone within this research are: 1) Observing, interviewing, documenting 2) Curating the mathematics model and 3) Optimizing profits. The research was conducted at GoGoCourse in 2018. It has shown that the offline classroom program of GoGoCourse has not run optimally which can be seen from the profit earned in 2018 at only Rp.83.508.400,- however in optimal level, the profit could reach Rp.175.155.000,-. The calculation is summed up from the total of 21 advance TOEFL classes, 9 IELTS classes, and 26 short courses classes.